Low-dose interleukin-2 therapy in refractory systemic lupus erythematosus: an investigator-initiated, single-centre phase 1 and 2a clinical trial. (September 2019) - Humrich, Jens Y; von Spee-Mayer, Caroline; Siegert, Elise; Bertolo, Martina; Rose, Angelika; Abdirama, Dimas; Enghard, Philipp; Stuhlmüller, Bruno; Sawitzki, Birgit; Huscher, Dörte; Hiepe, Falk; Alexander, Tobias; et al.
Summary: Background: An acquired deficiency of interleukin-2 (IL-2) and related defects in regulatory T cell homeostasis are thought to play a crucial role in the pathogenesis of systemic lupus erythematosus. We hypothesised that reconstitution of regulatory T-cell homoeostasis with low doses of IL-2 would be beneficial to patients with systemic lupus erythematosus. Methods: In this uncontrolled, phase 1 and 2a trial done in the Department of Rheumatology and Clinical Immunology at Charité—University Medicine Berlin (Berlin, Germany), we assessed the safety and tolerability of low-dose recombinant human IL-2 (aldesleukin) and its effects on regulatory T cells. We recruited patients aged 18–75 years with a confirmed diagnosis of systemic lupus erythematosus and moderate-to-severe disease activity despite previous treatment with at least two conventional therapies. Patients were given four cycles of low-dose aldesleukin daily for 5 days followed by a 9–16 day rest. The primary endpoints were safety and the number of patients who achieved at least a 100% increase in the proportion of CD25hi-expressing cells among circulating CD3 + CD4 + FOXP3 + CD127lo regulatory T cells at day 62 (ie, after four treatment cycles). Secondary endpoints included disease activity as measured by the Safety of Estrogens in Lupus National Assessment-Systemic Lupus Erythematosus Disease Activity Index (SELENA-SLEDAI) and the British Isles Lupus Assessment Group (BILAG) score, disease flares as measured by the SLEDAI flare index, auto-antibody and complement concentrations at day 62. Exploratory endpoints included various cellular and immunological parameters. The trial is registered with WHO/ICTRP, number DRKS00004858. Findings: Between March 31, 2014, and May 27, 2016, 13 patients were screened, of whom ten met eligibility criteria and were enrolled in the trial. Two additional patients were treated between April 1, 2013, and March 11, 2014, in a compassionate use setting. Eleven (92%) of the 12 patients achieved the primary endpoint. 159 adverse events were recorded, 75 (47%) of which were treatment related. Most treatment-related adverse events were transient and mild to moderate (grade 1–2). The most common adverse event was injection-site reaction (20%). No serious adverse events occurred during the treatment period. In ten (83%) of 12 patients, SELENA-SLEDAI scores were lower at day 62 than at baseline, and no severe disease flares were observed during the treatment period. Decreased disease activity correlated with the magnitude of increase in the proportion of activated regulatory T cells. IL-2 treatment resulted in a preferential proliferation of regulatory T cells that retained suppressive capacity. We observed decreases in cells that are involved in the regulation of germinal-centre reactions. Interpretation: Low-dose IL-2 therapy is safe and well tolerated and selectively promotes the expansion of functional regulatory T cells in patients with moderate-to-severe systemic lupus erythematosus. Low-dose IL-2 treatment might also be beneficial in reducing disease activity, although larger trials are needed to address efficacy. Funding: German Research Foundation.